Lejos: la distopía socialista-feminista de Caryl Churchill - Sotomayor-Botham, Paola (Revista Chilena de Literatura, 2013)
Far Away, one of only two plays by Caryl Churchill that have been performed in Chile, offers an alarming vision of the 21st century, which combines war and ecological disaster. In the theatre of this English dramatist, however, the presence of a frightening future operates asa warning in order to encourage social change. Using elements of Critical Feminist Theoryas well as the literary distinction between ‘dystopia’ and ‘anti-utopia’, this article argues that -despite certain ambiguities that have been detected by critics- Churchill’s work has notabandoned its progressive political ideals.